Challenges Healthcare Management Business: ISP Innovation SMEs with Technology Virtualization and Server Consolidation - Mahadewi, Erlina Puspitaloka; Mohamad Reza Hilmy; Arnastya Iswara Sanantagraha (International Journal of Science, Technology & Management, 2021)
The adaptation and innovation of the healthcare business strategy during the pandemic and new normal is needed now, for Small and Medium Enterprises (SMEs) which are engaged in Internet Service Providers (ISP) especially in running their business in pandemic also face the future challenging. This study aims to prove that virtualization technology planning, virtualization technology adaptability, and server consolidation services have a positive effect on healthcare management and business, such as operational costs with an impact on more efficient of healthcare small and medium enterprises (SMEs) Internet Service Providers (ISPs) in Indonesia. The data were taken from distributing questionnaires to 77 company representative respondents with the positions of IT Manager, IT Supervisor, and CIO. Data were analyzed by SEM using Smart PLS. The results of the research obtained prove that the operational cost effectiveness of Data Center management is influenced by planning, adaptability, and application of virtualization technology for 5.0. SMES ISPs in Indonesia healthcare sector need to pay attention to new result of planning, adaptability, and implementation of server consolidation services as a determinant of operational and cost effectiveness related to business objectives and management in managing a Data Center in the pandemic, new normal and future challenges.